Breast reconstruction with permanent expander: a different approach - Manfredini,Rinede Luis (2011)
BACKGROUND: Immediate or delayed breast reconstruction with tissue expanders can be performed in one or several surgical sessions. We opted to perform breast reconstruction over several sessions. The aim of this study was to report our experiences with the breast reconstruction technique involving Becker permanent tissue expanders and complete expander coverage with a flap comprising the pectoralis major, pectoralis minor, serratus anterior, and rectus abdominis aponeurosis. METHODS: The medical records of 21 patients who underwent postmastectomy breast reconstruction with Becker permanent tissue expanders were retrospectively analyzed. RESULTS: During muscle flap preparation, the aponeurotic dissection was performed 6-8 cm below the inframammary crease, aiming at full expander coverage without tension, enabling lower suturing in the inframammary crease, and avoiding disruption of the pectoralis major attachments. Only two patients developed infection, one in the first postoperative week and the other in the third postoperative month. CONCLUSIONS: The flap comprising the pectoralis major, pectoralis minor, serratus anterior, and rectus abdominis aponeurosis is a good choice for breast reconstruction with permanent tissue expanders because it ensures adequate expander and skin-flap protection. Moreover, the technique enables tissue expansion without confining the expanders in the submuscular cavity